Mapping The Agriculture Land of The Land Farmers in The South Coast of Kulon Progo - Indreswari Suroso; Ferry Setiawan (Journal of Applied Geospatial Information, 2023)
The south coast land of Kulon Progo on the beginning was sandy and infertile soil. The land then was converted into agriculture land, chilli farm based on the idea of the agriculture expert, Mr. Karman. This study aimed to map the agriculture land in Bidadara coast, Panjatan district, Kulon Progo because of the the success of the coastal farmers on producing an abundance of chilli harvest. The method used was interviews and field observation. The deviced used for mapping was DJI Mavic 2 Pro multicopter drone operated approximately for 20 minutes. The result of this study was aerial photos of drone shots with a height of 20 meters, 30 meters, and 50 meters above ground level onto the soil conditions adjacent to Bidara Beach, Panjatan, Kulon Progo. It was seen that the stretch of coastal land was planted with coconut trees and chilies. Hence, no wonder that the coastal land farmers are rich because of fantastic income from the farm. It is proven that the cultivation of this chili plant can improve the economy of the farming community on the South Coast of Kulon Progo.